2015 International Conference on Information Technology Systems and Innovation (ICITSI) 2015
DOI: 10.1109/icitsi.2015.7437722
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment model of application development using Bayesian Network and Boehm's Software Risk Principles

Abstract: There are many risks involved in developing highly qualified application that need to be carefully managed. Hence, the robustness of assessment and risk management based on valid evidence and valid information is a key driver and mandatory. This study aims to develop a risk assessment model that can be used to analyze the interrelationship between risks and calculates the probability and impact of risks. In this study we use Bayesian Network (BN) and Boehm's Software Risk Principles. Finally, we proposed new r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The obtained grouping is shown in Table 1 to explain the relationship between risk areas. This result can also be seen in our previous research [10]. With this grouping, one can create a dependency model based on interrelation of risk category area shown in Figure 1.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The obtained grouping is shown in Table 1 to explain the relationship between risk areas. This result can also be seen in our previous research [10]. With this grouping, one can create a dependency model based on interrelation of risk category area shown in Figure 1.…”
Section: Methodssupporting
confidence: 81%
“…Based on these research result, we enhance the work of [7] to show the possibility of relation between the top 20 risks. Earlier effort on this topic can be seen in [10] where the theoretical background, context diagram, mapping table, and preliminary model were elaborated. Our paper investigates further on how to determine the probability and interrelationship of such risk in application development using Bayesian network concept.…”
Section: Introductionmentioning
confidence: 99%
“…• A3 -Risk identification: This is the process that makes it possible to find, recognise, and describe the different risks, the sources of the risks, and the events, in addition to identifying each of the causes and their potential consequences. Sipayung et al [56] define risk identification as an early stage in risk assessment which often allows the risks involved in the development projects for applications to be pinpointed. The authors use a set of risks identified in software projects as a guide in this stage; these are listed in [117].…”
Section: Tablementioning
confidence: 99%
“…Sipayung et al [56] contribute by presenting a model that enables calculation of the probability and impact of risk in application development projects. This probability is calculated using Bayesian networks.…”
Section: Rq4mentioning
confidence: 99%
“…The boom of the network security situation awareness has been laid out. In the past two decades, the experts and scholars not only use Analytic Hierarchy Process (AHP) [2,3], attacking graph [4,5], and Bayesian network [6,7] to study the risk assessment but also make use of the hidden Markov model [8,9] to discuss the field. With the advent of Computer Immunology, the researchers began to study the domain based on artificial immune [10,11], such as that based on antibody concentration [12] of network risk assessment.…”
Section: Introductionmentioning
confidence: 99%